DFI Funding and Infrastructure Development: A case of the under-resourced Municipalities in South Africa - Kgomo,Elizabeth (Graduate School of Business (GSB), 2021)
Abstract Despite powers and resources given to local authorities to deliver and manage their own resources, most municipalities still struggle to achieve their objectives as set out in the South African constitution. This research study sought to investigate and establish whether the infrastructure development funding by DFIs e.g. the DBSA invested in some of the under-resourced municipalities in all the provinces of the country has resulted in improved service delivery and upliftment of the socioeconomic standard of their communities and if not, what the specific reasons are. A qualitative research methodology was conducted because the objective was to get the opinions and experiences of the under resourced municipalities throughout all the nine provinces of South Africa. The results of the study indicated that municipalities are very aware of the role of DFIs and all the municipalities that participated in the study stated that they had received development loans from the DBSA. The results of this study also revealed that all the respondents indicated that development finance they received made a significant difference in improving infrastructure developments in their municipalities. It has advanced and uplifted the socio economic statuses of the communities and improved service delivery and quelling the frequency and severity of service delivery protests. Poor governance was a serious impediment in municipalities where lack of accountability, lack of leadership, tensions between political and administrative interface; poor ability of many councillors to deal with the demands of local government; lack of clear separation of roles between the legislative and executive; inadequate accountability measures and support systems and resources for local democracy and poor compliance with the legislative and regulatory frameworks for municipalities and fraud and corruption are among the key governance challenges faced by municipalities